Toddler growth and development monitoring training in efforts to prevent stunting incidents in Wonorejo Village, Sukoharjo Regency - Sunarti Sunarti; Iis Wahyuningsih; Endah Sulistiawati; Nuratul Mutmainnah; Erlina Aprilia Damayanti (Community Empowerment, 2024)
Stunting remains a significant problem in Indonesia, but early detection can prevent many cases. Regular monitoring of toddlers' growth and development is crucial. However, a common challenge is the lack of competency among community health workers (cadres) in performing this monitoring. This community service aimed to train posyandu cadres in monitoring children's growth and development using a hands-on, learning-by-doing approach. Training involved lectures, discussions, and practical application of anthropometric methods to assess nutritional status. Results showed a statistically significant increase in average knowledge scores from 64.52 ± 12.86 SD to 71.94 ± 16.00 SD. Despite this improvement, some cadres still require further training. This community service demonstrates that training can effectively increase posyandu cadres' knowledge of children's growth and development.